MOR: Uma Ferramenta para o Mapeamento Objeto-Relacional em Java - Murta, Leonardo Gresta Paulino; Veronese, Gustavo Olanda; Werner, Cláudia Maria Lima (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2001)
This work presents an approach to map Java objects into relational databases. This approach is transparent because does not require any extra code. It uses the reflection mechanism to know what information exists inside the objects and the Java Database Connection (JDBC) to connect with the different databases.